An Evaluation and Support of Usability of Hacettepe University Libraries’ Websites through Training: A Study on Students of Hacettepe University, the Department of Information Management - Emine Cengiz (Türk Kütüphaneciliği)
This study has been conducted with the aim of testing the characteristics of usage and evaluating the effects of user education on web site use through assessment of website of Hacettepe University Libraries. In the study conducted on eight volunteer subjects who are users of the website of the University Libraries, qualitative and quantitative research methods were used collectively. During the application of the traditional usability test, six tasks were given to the associations, requiring them to use various sections of the website of the university library. During the responding period of the questions; the data obtained from loud-thinking technique, click counts and response times were recorded. Afterwards, the subjects were provided with a training by a librarian. The quantitative and qualitative data obtained at the end of the study were analyzed and the positive and negative features affecting the use of the website were determined. According to the research results, it was hard for them to answer the questions of the pre-screening of the user catalog, database access, and problems finding the article before the training. Support through training for associations has positively affected the usability of the website. According to the findings, it is suggested that users should be trained on using the website during training programs, catalog section should be more promoted and highlighted, the terminology should be reviewed and a subject search engine should be created in the databases section.